In vivo antimicrobial activity of silver nanoparticles produced via a green chemistry synthesis using Acacia rigidula as a reducing and capping agent - Escárcega González, Carlos Enrique; Garza Cervantes, Javier Alberto; Vázquez Rodríguez, Augusto; Montelongo Peralta, Liliana Zulem; Treviño Gonzalez, Mario Tadeo; Díaz Barriga Castro, Enrique; Saucedo Salazar, Esmeralda M; Chávez Morales, Rosa María; Regalado Soto, Diana Ivette; Treviño González, Francisco Moises; Carrazco Rosales, Jose Luis; Villalobos Cruz, Rocío; et al. (Dove Medical Press, 2018)
Introduction: One of the main issues in the medical field and clinical practice is the development of novel and effective treatments against infections caused by antibiotic-resistant bacteria. One avenue that has been approached to develop effective antimicrobials is the use of silver nanoparticles (Ag-NPs), since they have been found to exhibit an efficient and wide spectrum of antimicrobial properties. Among the main drawbacks of using Ag-NPs are their potential cytotoxicity against eukaryotic cells and the latent environmental toxicity of their synthesis methods. Therefore, diverse green synthesis methods, which involve the use of environmentally friendly plant extracts as reductive and capping agents, have become attractive to synthesize Ag-NPs that exhibit antimicrobial effects against resistant bacteria at concentrations below toxicity thresholds for eukaryotic cells. Purpose: In this study, we report a green one-pot synthesis method that uses Acacia rigidula extract as a reducing and capping agent, to produce Ag-NPs with applications as therapeutic agents to treat infections in vivo. Materials and methods: The Ag-NPs were characterized using transmission electron microscopy (TEM), high-resolution TEM, selected area electron diffraction, energy-dispersive spectroscopy, ultraviolet–visible, and Fourier transform infrared. Results: We show that Ag-NPs are spherical with a narrow size distribution. The Ag-NPs show antimicrobial activities in vitro against Gram-negative (Escherichia coli, Pseudomonas aeruginosa, and a clinical multidrug-resistant strain of P. aeruginosa) and Gram-positive (Bacillus subtilis) bacteria. Moreover, antimicrobial effects of the Ag-NPs, against a resistant P. aeruginosa clinical strain, were tested in a murine skin infection model. The results demonstrate that the Ag-NPs reported in this work are capable of eradicating pathogenic resistant bacteria in an infection in vivo. In addition, skin, liver, and kidney damage profiles were monitored in the murine infection model, and the results demonstrate that Ag-NPs can be used safely as therapeutic agents in animal models. Conclusion: Together, these results suggest the potential use of Ag-NPs, synthesized by green chemistry methods, as therapeutic agents against infections caused by resistant and nonresistant strains. Keywords: silver nanoparticles, green synthesis, in vitro antibacterial activity, in vivo antibacterial activity, skin infection, toxicological study